A comparison of material models for the simulation of selective beam melting processes - Burkhardt, Christian; Soldner, Dominic; Mergheim, Julia (Procedia CIRP, 2020)
The focus of this contribution lies on the comparison of different material models for the thermo-mechanical simulation of selective laser melting (SLM) processes. A Finite Element (FE) framework for the analysis of residual stresses and distortions in laser beam melting processes is introduced. The FE solver for the thermo-mechanical problem uses a staggered algorithm, is based on the open source finite element library deal.ii and makes use of heavy parallelization. The most important aspects to be investigated here are the mechanical material behavior and stress relaxation in the range of the melting temperature. Material models, which reset certain variables as stress and plastic strain to zero at a critical temperature are compared to a thermo-viscoplastic constitutive law. Simulations, related to the SLM process of Ti-6Al-4V, are performed to compare the residual stresses and plastic strains predicted by different models after melting and cooling. Furthermore, the validity of geometrically linearized material model is analyzed. <br
Keywords: SLM process; Finite Element simulations; residual stresses; viscoplastic material models; melting; solidification